2005
DOI: 10.1001/archinte.165.10.1154
|View full text |Cite
|
Sign up to set email alerts
|

Bezafibrate for the Secondary Prevention of Myocardial Infarction in Patients With Metabolic Syndrome

Abstract: Bezafibrate reduces the incidence of MI in patients with MS during long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
165
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 289 publications
(175 citation statements)
references
References 44 publications
8
165
1
1
Order By: Relevance
“…Bezafibrate and fenofibrate have some evidence of preventing coronary artery disease in Bezafibrate Infarction Prevention (BIP) [21,22] and Fenofibrate Intervention and Event Lowering in Diabetes (FIELD) Study [23], respectively. Our present data indicate that fenofibrate treatment (200 mg per day for 8 weeks) produced more favorable effects on cholesterol metabolism than did bezafibrate treatment (400 mg per day for 8 weeks) with regard to lower TC, non-HDL-C, LDL-C and apolipoprotein B levels.…”
Section: Discussionmentioning
confidence: 99%
“…Bezafibrate and fenofibrate have some evidence of preventing coronary artery disease in Bezafibrate Infarction Prevention (BIP) [21,22] and Fenofibrate Intervention and Event Lowering in Diabetes (FIELD) Study [23], respectively. Our present data indicate that fenofibrate treatment (200 mg per day for 8 weeks) produced more favorable effects on cholesterol metabolism than did bezafibrate treatment (400 mg per day for 8 weeks) with regard to lower TC, non-HDL-C, LDL-C and apolipoprotein B levels.…”
Section: Discussionmentioning
confidence: 99%
“…1 Moreover, further subanalyses demonstrated that the administrations of bezafibrate significantly reduced new-onset diabetes 2,3 and myocardial infarction in the patients with the metabolic syndrome (MS). 4 The Fenofibrate Intervention and Event Lowering in Diabetes (FIELD) study showed that fenofibrate significantly reduced nonfatal myocardial infarctions and coronary revascularizations, a secondary endpoint, among patients with type 2 diabetes. 5 These favorable clinical outcomes in fibrate studies might be explained by not only its triglyceride-lowering effect but also its various PPAR␣-mediated pleiotropic effects.…”
mentioning
confidence: 99%
“…Emerging varied areas of current MS research interests include heterogeneous topics like adiponectin and biomarkers preserving endothelial health [33,34], angiotensinogen, resistin, and leptin secretion [33], nonalcoholic fatty liver disease and liver steatosis [35], hyperuricemia [36], genetic predisposition [37], the role of adypocytokines and neurohumoral dysregulation [38]; sleep disorders and ethnicity [39], the possible ways for treatment optimization in patients with CVD [40]. Additional related matters are currently investigated, like heart rate (HR) turbulence; it has been shown that this turbulence -a well-established predictor of cardiac autonomic dysfunction -is significantly impaired in MS patients without T2DM in adults [41].…”
Section: Prosmentioning
confidence: 99%